2015
DOI: 10.1080/0305764x.2015.1067289
|View full text |Cite
|
Sign up to set email alerts
|

The inclusion of pseudowords within the year one phonics ‘Screening Check’ in English primary schools

Abstract: This cover sheet may not be removed from the document.Please scroll down to view the document. THE INCLUSION OF PSEUDOWORDS WITHIN THE YEAR ONE PHONICS 'SCREENING CHECK' IN ENGLISH PRIMARY SCHOOLS Howard Gibson and Jennifer England AbstractThe paper highlights problems surrounding the Year 1 Phonics Screening Check that has accompanied the legislative framework for synthetic phonics in English primary schools. It investigates the inclusion of pseudowords and raises questions regarding their generation and cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The test has always been and remains controversial, due to long‐standing debates about the efficacy of synthetic phonics (see Wyse & Goswami ; Clark, , ), doubts about the role of the check in identifying children who struggle with phonics (Duff et al ., ) and the inclusion of pseudo‐words (Gibson & England, 2014, ). The aim of the policy is ostensibly to improve reading scores, by ‘[making] sure that all pupils have learned phonic decoding to an appropriate standard by the age of 6’ (DfE, ), although the increased role of synthetic phonics in teaching children to read continues to be the subject of fierce debate (Davis, ; Clark, ).…”
Section: Introductionmentioning
confidence: 99%
“…The test has always been and remains controversial, due to long‐standing debates about the efficacy of synthetic phonics (see Wyse & Goswami ; Clark, , ), doubts about the role of the check in identifying children who struggle with phonics (Duff et al ., ) and the inclusion of pseudo‐words (Gibson & England, 2014, ). The aim of the policy is ostensibly to improve reading scores, by ‘[making] sure that all pupils have learned phonic decoding to an appropriate standard by the age of 6’ (DfE, ), although the increased role of synthetic phonics in teaching children to read continues to be the subject of fierce debate (Davis, ; Clark, ).…”
Section: Introductionmentioning
confidence: 99%
“…When presented with words for which they have no semantic association or sight word recognition, children are required to apply their knowledge of grapheme-phoneme correspondences to "decode" the word. The same methodology underpins the Phonics Screening Check, which has been used in England since 2012 (Gibson & England, 2016) and is now in use across South Australia (Government of South Australia Department for Education, 2019). Word-level reading tasks that include both real word and pseudoword components can enable teachers to more accurately identify specific difficulties and to select interventions capable of targeting specific areas of weakness (Castles, Polito, Pritchard, Anandakumar, & Coltheart, 2018).…”
Section: Phonemic Decoding and Word Recognitionmentioning
confidence: 99%
“…Whilst this may be resisted, as it is stated that the purpose of the pseudo words is to ensure that no child can ‘sight read' the words and so bypass the application of phonics skills, it is important for policy‐makers to balance the negative unintended outcomes of using pseudo words with any positive outcomes in relation to reading attainment (of which there is no current evidence). Gibson and England () and later, the Darnell et al () research concluded that there was little or no difference between using real or non‐words in phonics assessment and so the replacement of non‐words with real words would not compromise the assessment of phonics skills and knowledge. Because of the high stakes nature of the PSC, pseudo words are being taught as the curriculum rather than being used as an assessment tool.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%